Gender and agrarian reforms - Jacobs, Susie M. (Routledge international studies of women and place, 2009)
This book presents an overview of gender and agrarian reform experiences globally, highlighting case studies from Latin America, Asia, Africa and Eastern Europe. Jacobs also compares agrarian and land reforms organized along collective lines as well as those organizing along individual household lines.